METODE PENGAJARAN PONDOK PESANTREN : STUDI KASUS KH. YAHYA MASDUQI DALAM KAJIAN KITAB TAFSIR AL-JALALAIN YANG DITERAPKAN DI PONDOK PESANTREN MIFTAHUL MUTA’ALLIMIN BABAKAN CIWARINGIN CIREBON - hisyam nur (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2023)
The Qur'an is the consensus of the majority of scholars that the Word of Allah in the form of a miracle was revealed to the cover of the Prophets and Apostles, through the intercession of the Angel Gabriel (as), written in the manuscripts narrated to us with mutawatir. Reading it is worship, which begins with Surah Al-Fatihah and ends with Surah An-Nas. This study aims to describe: first how the teaching method of KH. Yahya Masduqi in the study of the book of Tafsir Jalalain, secondly how the students' understanding of the study of the book of Tafsir Jalalain, thirdly the relevance of the teaching method of the book of Tafsir Jalalain at the Miftahul Muta'allimin Islamic Boarding School, Ciwaringin Cirebon. This study uses a qualitative method with a descriptive approach, taking the background of the Miftahul Muta'allimin Islamic Boarding School in Babakan Ciwaringin Cirebon. Data collection is done by conducting observations, interviews and documentation. Data analysis is done by giving meaning to the data that has been collected, and from that meaning conclusions are drawn. The results showed: first, the study method of the Jalalain interpretation book at the Miftahul Muta'allimin Islamic Boarding School was very varied, not only using the traditional method but also inserted with the modern method. and in Relevance only use the Bandungan and Deliberation method in the study of Jalalain's interpretation. Keywords: Method, Al-Jalalain's Tafsir